Trade Openness and Inflation Episodes in the OECD. - Bowdler, C; Nunziata, L (Ohio State University Press, 2006)
Boschen and Weise (Journal of Money, Credit, and Banking, 2003) model the probability of a large upturn in inflation in the OECD (an inflation start). We extend their work to consider the impact of trade openness on the probability of such an event. The main finding is that increased openness reduces the probability of an inflation start, both directly, and indirectly through restricting the role of general elections in triggering inflation starts.